PENGARUH PEMBERIAN CUKA APEL DAN GARAM DALAM PENGURANGAN RESIDU PESTISIDA PADA TANAMAN CABAI MERAH (Capsicum annum L) - Fatma, Fitria; Aprilliani, Cici (HUMAN CARE JOURNAL, 2025)
Pesticides are synthetic substances that contain harmful chemicals used in agriculture, including red chili cultivation. According to the World Health Organization (WHO) data from 2014, pesticide poisoning incidents were prominent, particularly in developing countries, accounting for 80% of cases. Excessive pesticide residues in consumed crops have been linked to health issues such as cancer, with breast cancer being one of the most notable, accounting for 43.3% of cases. The purpose of this study was to investigate the impact of applying apple cider vinegar and salt in reducing pesticide residues in red chili plants in 2023. This research employs a quantitative approach with an observational design and pure experimental laboratory tests involving the Paired T-test. Red chili samples weighing 1050 grams were collected in July and subjected to different time variations of 10, 15, and 20 minutes in the laboratory. Based on pre-treatment statistical tests, the average pesticide residue was found to be 0.544 mg/kg. After the application of apple cider vinegar for 10 minutes, the residue reduced to 0.255 mg/kg, for 15 minutes it reduced to 0.345 mg/kg, and for 20 minutes it reduced to 0.459 mg/kg. Similarly, when salt was applied for 10 minutes, the residue decreased to 0.524 mg/kg, for 15 minutes it decreased to 0.458 mg/kg, and for 20 minutes it decreased to 0.407 mg/kg.The study's conclusion is drawn from the analysis of 7 samples treated with apple cider vinegar and salt, revealing a p-value of 0.000 (Ho Rejected). This indicates that the application of apple cider vinegar and salt has a significant effect on reducing pesticide residues in red chili.